Feasibility and pilot efficacy of cognitive remediation for people in residential substance use treatment. (29th March 2021) - Allan, Julaine; Thompson, Anna; Carlyle, Molly; Thomas, Matthew; Medalia, Alice
Abstract: Introduction: There are high rates of cognitive impairment among people seeking treatment for problematic substance use, which is rarely addressed in treatment programs. The aim of this pilot study was to evaluate the feasibility and outcomes of the neuropsychological and educational approach to cognitive remediation (NEAR) in a residential substance treatment setting. Methods: A non‐randomised trial conducted between November 2018 and November 2019, compared outcomes for 34 residents who received cognitive remediation (CR) plus treatment as usual (TAU) to 31 residents who received TAU only. Number of groups and attendance, and a measure of client satisfaction assessed feasibility. Cognitive function was assessed at baseline (service admission), and at 2 and 6 months post‐admission. Results: A total of 95 CR groups were delivered over a 36‐week time period with a high degree of treatment fidelity and acceptability to participants. Cognitive outcomes improved across both the CR+TAU and TAU groups by 2 months, which was maintained at 6 months for outcomes related to executive functioning. There were no significant differences between the CR+TAU and TAU groups at 2 or 6 months, although a large effect size and confidence intervals indicated a potentially larger change in cognitive flexibility after receiving CR. Discussion and Conclusions: This study contributes to our understanding of the implementation of CR in the alcohol and other drug rehabilitation setting. It is feasible to incorporate the NEAR program in treatment. The small sample size and lower than expected treatment dose likely contributed to the lack of significant findings.